Pengaruh Media Sosial terhadap Prestasi Belajar dan Minat Belajar Anak di SMP Negeri 3 Kinali - Gusnita, Putri; Afrinaldi, Afrinaldi; Yusri, Fadhilla; Rahmi, Alfi (YASIN, 2025)
This study is driven by growing concerns over the widespread influence of social media in students’ lives and its impact on academic performance and learning interest. Phenomena such as declining academic achievement and reduced concentration due to notification distractions during study sessions have become significant issues in educational settings. The purpose of this study is to examine the influence of social media on students' academic performance and learning motivation at SMP Negeri 3 Kinali. A quantitative approach was employed using simple linear regression analysis. The sample consisted of 35 randomly selected students from a total population of 136. A Likert-scale questionnaire was used as the research instrument, and data were analyzed using an F-test. The findings indicate that social media significantly affects students' academic performance, with an F-value of 424.674 > F-table value of 4.15 and a significance level of 0.0001. The impact on learning motivation is also significant, as shown by an F-value of 246.006 > F-table value of 4.15 and a significance level of 0.000 < 0.05. Based on these results, the alternative hypothesis is accepted and the null hypothesis is rejected. The study concludes that uncontrolled use of social media negatively affects students’ academic performance and learning motivation. The implications suggest the need for intensive supervision by teachers and parents regarding social media use, as well as the importance of integrating educational approaches to promote its constructive use in the learning process.